Multi-model Arlequin approaches for fast transient, FSI-oriented, fluid dynamics with explicit time integration. (15th March 2020) - Fernier, Alexandre; Faucher, Vincent; Jamond, Olivier
Highlights: A new approach for coupling overlapping models in fluid dynamics is proposed. It associates famous Arlequin and Chimera methods. Stability of the coupled framework with explicit time integration is proved. Accuracy and mesh convergence are demonstrated on significant examples. Abstract: The simulation of accidental transient sequences in the nuclear industry requires, even at a global scale, for local geometric details to be taken into account. Multi-model approaches allow the integration of such details without modifying the global scale modelling (techniques also known as numerical zooms). In the current paper, we propose two new multi-model approaches for transient fluid dynamics described by the Euler equations. This is done with the additional purpose of developing multi-model approaches for Fluid Structure Interaction (FSI) phenomenons so that a hybrid Finite Element/Finite volume discretization is used for the fluid. Both proposed multi-model approaches use the Arlequin framework for the treatment of the momentum equation while the other two equations are treated by either the Chimera method or the Arlequin method. As explicit time integrators are used, a stability study is completed and guidelines are given in order to guarantee a feasible time step. In particular, the choice of the Arlequin weight functions should be defined carefully. Spurious effects are observed and their origin explained. An approach to efficiently handle them is proposed. Two convergence studies validate the proposed approaches and present similar, if not better, convergence properties than for the Chimera method, currently the reference in the literature. Thus, these two approaches should be considered for transient fluid dynamics applications.